1999
DOI: 10.1002/(sici)1097-0142(19990115)85:2<295::aid-cncr5>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, 5-fluorouracil, and cisplatin combination chemotherapy for the treatment of advanced gastric carcinoma

Abstract: BACKGROUND Although the clinical efficacy of paclitaxel in the treatment of gastric carcinoma has not been clearly defined, recent reports have suggested a possible role in the treatment of upper gastrointestinal carcinomas in vitro and in vivo. In this study, the authors evaluated the efficacy and toxicity of a combination chemotherapy that included paclitaxel, 5‐fluorouracil (5‐FU), and cisplatin in the treatment of patients with advanced gastric carcinoma. METHODS Forty‐one gastric carcinoma patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…An objective response rate of 51% -or 58% if only those patients receiving at least one complete cycle of therapy are taken into accountincluding 11% (13%) complete remissions in chemonaive gastric cancer patients demonstrates the high activity of this regimen. A similar favourable response rate of 51% with a median survival time of 6 months was recently achieved by Kim et al (1999) administering paclitaxel at a dose of 175 mg/m 2 on day 1, 5-FU at a dose of 750 mg/m 2 on days 1-5 as continuous infusion and cisplatin at a dose of 20 mg/m 2 as a 30 minute infusion on days 1-5. In patients with adenocarcinoma of the oesophagus, Ilson et al (1998) reported a response rate of 46% with a similar schedule.…”
Section: Discussionmentioning
confidence: 53%
“…An objective response rate of 51% -or 58% if only those patients receiving at least one complete cycle of therapy are taken into accountincluding 11% (13%) complete remissions in chemonaive gastric cancer patients demonstrates the high activity of this regimen. A similar favourable response rate of 51% with a median survival time of 6 months was recently achieved by Kim et al (1999) administering paclitaxel at a dose of 175 mg/m 2 on day 1, 5-FU at a dose of 750 mg/m 2 on days 1-5 as continuous infusion and cisplatin at a dose of 20 mg/m 2 as a 30 minute infusion on days 1-5. In patients with adenocarcinoma of the oesophagus, Ilson et al (1998) reported a response rate of 46% with a similar schedule.…”
Section: Discussionmentioning
confidence: 53%
“…This impedes the long-term treatment (3). Therefore, the development of anti-cancer treatments by which the toxicity can be lowered and the quality of life can be improved has been continually made (1).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Thus-Patience et al proposed that a single use of DF except for cisplatin had an equivalent profile of the efficacy to epirubicin + cisplatin +5-FU (ECF) or DCF (2). According to various types of Phase II studies, a combination treatment with Paclitaxel produced a response rate of 32�66% and a survival period of 6�12 months (3)(4)(5). To date, however, almost no randomized clinical trials have been attempted to compare the efficacy of these regimen.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the paclitaxel and 5-FP combination produced a 51% objective response, which suggests that taxane is efficacious in gastric cancer (Kim et al, 1999). Docetaxel, a semi-synthetic analogue of paclitaxel, was reported to offer superior response rates and a longer time to progression when added to the FP regimen (5-FU/cisplatin) than FP alone in a randomised phase III trial .…”
mentioning
confidence: 92%